2018
DOI: 10.1136/bmjopen-2017-017385
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of the differential impact of time-varying depressive symptoms on all-cause and cause-specific mortality by health status in community-dwelling adults: the REGARDS study

Abstract: ObjectiveTo assess the association between time-varying depressive symptoms with all-cause and cause-specific mortality.DesignThe REGARDS (Reasons for Geographic and Racial Differences in Stroke) is a national, population-based longitudinal study conducted from 2003 to 2007.SettingGeneral continental US communities.Participants29 491 black and white US adults ≥45 years randomly sampled within race–sex–geographical strata.ExposureElevated depressive symptoms (Centre for Epidemiologic Studies Depression (CES-D) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 36 publications
4
26
1
3
Order By: Relevance
“…Strong associations between elevated depressive symptoms and deaths from all-causes, CVD, and non-CVD, non-cancer in our study agree with previous studies among older adults [ 40 42 ]. Behavioural mechanisms could be a potential explanation for the association between depression and all-cause and CVD mortality; depressed individuals are more likely to be physically inactive, to smoke, and to have unhealthy diet [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Strong associations between elevated depressive symptoms and deaths from all-causes, CVD, and non-CVD, non-cancer in our study agree with previous studies among older adults [ 40 42 ]. Behavioural mechanisms could be a potential explanation for the association between depression and all-cause and CVD mortality; depressed individuals are more likely to be physically inactive, to smoke, and to have unhealthy diet [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Individuals with depression are more likely to experience social isolation, decreased work performance, anxiety, and substance use disorder, and are more likely to attempt suicide [13][14][15]. They are also more likely to develop cardiovascular disease and diabetes, and have higher all-cause mortality than individuals without depression [19,[48][49][50][51]. Productive years lost due to disability from depression are greater than those from diabetes, cardiovascular disease, and cancer [52].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous research has shown differential effects of race and sex with depressive symptoms on aortic calcification (Lewis, Everson-Rose, Colvin, Matthews, Bromberger & Sutton-Tyrrell, 2009), relationships specifically to weathering have not been shown. It is well-known that depression is associated with poor health, both prospectively (Moise, Khodneva, Jannat-Khah, Richman, Davidson & Kronish, 2018) and retrospectively, but relatively little is known about racial differences in these associations. One observational study found that retrospective and prospective associations between depressive symptoms and number of chronic medical conditions were present for Whites, but not Blacks (Assari et al, 2015) Other recent observational studies have found that depressive symptoms were more predictive of mortality in Whites than Blacks (Assari, 2018, Assari et al, 2016) but a different observational study found that depressive symptoms were associated with incident coronary heart disease in Blacks but not Whites (Sims, Redmond, Khodneva, Durant, Halanych & Safford, 2015).…”
Section: Discussionmentioning
confidence: 99%